ANALISIS TINGKAT KESULITAN SISWA DALAM MEMAHAMI NILAI TEMPAT SERTA MEMBACA & MENULIS BILANGAN CACAH DI KELAS IV MI FATHUL HUDA SUMENGKO - Dia Kartika, Amelia; Fitriatun Rodiyah, Ira; Andara Lucky Dwi Septiana, Rivana; ningrum, Sefira; Khoiriyyah, Wafirotul (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to describe the level of difficulty of students in grade IV of MI Fathul Huda Sumengko in understanding the concept of place values, reading numbers, and writing integers, as well as testing the validity and reliability of the test instruments used. This study is a quantitative descriptive research with 19 students. Data was collected through a written test of 20 questions that included three indicators, namely place values, reading numbers, and writing numbered numbers. The validity test of the question item was carried out using the Pearson correlation technique (item-total), while the reliability test was carried out with Cronbach's Alpha technique. The results showed that of the 20 questions, 9 were declared valid and 11 were declared invalid, with an instrument reliability coefficient of 0.701 which was classified as high/reliable. The test results showed an average student score of 86.32 with a completion percentage of 84.21% based on the Minimum Completeness Criteria (KKM) of 75. Analysis of the difficulty level per indicator showed that the number writing indicator had the highest difficulty level (9.65%), followed by reading numbers (8.77%), and place values (7.24%). These findings indicate that students still have relatively greater difficulty in writing number symbols from verbal descriptions than reading them, so learning reinforcement is needed that emphasizes understanding of concepts, not just procedural memorization.